2007
DOI: 10.1038/sj.jp.7211747
|View full text |Cite
|
Sign up to set email alerts
|

Severe early onset pre-eclampsia: prognostic value of ultrasound and Doppler assessment

Abstract: Objective: Assess the prognostic value of ultrasound and Doppler parameters in severe preterm pre-eclampsia.Study design: Prospective cohort study in Cape Town, South Africa, involving 113 women with severe pre-eclampsia between 24 and 34 weeks of gestation and managed expectantly when suitable. Serial ultrasound and multivessel Doppler assessments were performed 2 to 3 times weekly. Observations included fetal weight estimation, growth pattern, amniotic fluid volume, appearance of the heart and bowel, pulsati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Also, regional brain perfusion studies in IUGR fetuses showed that brain hypoxia is present long before 11 significant changes in MCA are observed [23] . In keeping with this, Geerts and Odendaal [24] found that in severe PE, umbilical and cerebral Doppler parameters were not associated with adverse outcome, once adjusted for fetal size. On the contrary, our multivariate analysis that included SGA as a covariate confirmed the significant and independent value of UtA Doppler in predicting adverse outcome.…”
Section: Discussionmentioning
confidence: 78%
“…Also, regional brain perfusion studies in IUGR fetuses showed that brain hypoxia is present long before 11 significant changes in MCA are observed [23] . In keeping with this, Geerts and Odendaal [24] found that in severe PE, umbilical and cerebral Doppler parameters were not associated with adverse outcome, once adjusted for fetal size. On the contrary, our multivariate analysis that included SGA as a covariate confirmed the significant and independent value of UtA Doppler in predicting adverse outcome.…”
Section: Discussionmentioning
confidence: 78%
“…Preeclampsia is characterized by placental insufficiency, mainly during early onset [8], which has been associated with low placental angiogenesis [3,4,6,28]. We have studied the cell proliferation/migration of HUVECs as the initial steps linked with angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Both a reduction in placental blood flow and impaired placental structure have been associated with neonatal complications following preeclampsia, such as growth retardation [4][5][6][7]. Specifically, Doppler studies reveal that impaired feto-placental blood flow is mainly evident in women with early-onset preeclampsia (EOPE) [8] rather than late-onset preeclampsia (LOPE) [9]. Moreover, EOPE exhibits placental histological changes related with reduced perfusion [10][11][12][13] as well as the anomalous structure of the peripheral villi and vasculature compared to respective controls identified by stereological analysis following EOPE, but not LOPE [13].…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical artery Doppler velocimetry provides an indirect measure of downstream vascular resistance in the fetoplacental vasculature 2 . Pregnancies complicated by severe early-onset forms of preeclampsia (PE) 3 and/or intrauterine growth restriction (IUGR) 4 typically exhibit increased resistance in the umbilical circulation, with absent or even reversed end-diastolic flow velocity. These highly abnormal Doppler flow patterns are associated with a poor perinatal prognosis, 5 in part because they identify a subset of pregnancies with chronic fetal hypoxia, metabolic acidosis, and reduced circulating glucose and amino acid levels 6–8 …”
mentioning
confidence: 99%